Pengaruh Penggunaan Birth Ball dan Aromaterapi Lavender Dalam Menurunkan Nyeri Persalinan Kala I Fase Aktif di RSUD Sultan Muhammad Jamaludin I Tahun 2025 - Isty Hafizah; Hidayani Hidayani; Maryam Syarah (Universitas Muhammadiyah Manado, 2025)
The process of labor is identical to the pain or pain that will be experienced. One method to overcome pain in a non-pharmacological way is the distraction method with birth ball which can reduce physiological pain, stress and anxiety. In addition, other non-pharmacological labor pain management is using lavender aromatherapy. This study aims to determine the effect of using birth ball and lavender aroma therapy in reducing labor pain during the active phase I at Sultan Muhammad Jamaludin I Hospital in 2025. This study used a qualitative approach with a case study approach. The population in this study were laboring mothers with normal labor status in the delivery room of the Sultan Muhammad Jamaludin I Hospital in February 2025. The sample in this study were 2 respondents of active phase I laboring mothers, namely 1 respondent to be given an intervention using birth ball and 1 respondent given an intervention using Lavender Aromatherapy.The results showed that the use of birth ball was effective in reducing labor pain during the active phase I at Sultan Muhammad Jamaludin I Hospital in 2025. After three observations, the pain score dropped from 8 to 5. The same thing happened with Lavender Aromatherapy, which also showed effectiveness in reducing pain, with the score dropping from 9 to 5. Comparison between the two methods showed a difference in the level of pain reduction by 1. Therefore, birth ball and Lavender Aromatherapy can be used as non-pharmacological methods to reduce labor pain, with the selection of methods adjusted based on individual comfort and response.